OPTIMASI KETEBALAN INSULATOR PADA JARINGAN PIPA GEOTHERMAL - Isnani, Isnani (MATEMATIKA, 2005)
Geothermal is one of cheap and huge energy resaources in Indonesia. Geothermal power supply generated by thermal steam, where is transmitted through geothermal pape line was usually built nearÂ  a geothermal source. To minimize heat losses pipe surface is patched by insulator. Furthermore to decide insulator thickness for optimum result, the mathematical model is applied. The insulator optimum thicknes Â (5,733575488) is obtained the cost needed is $1488,373278